Dual-readout aptasensing of antibiotic residues based on gold nanocluster-functionalized MnO2 nanosheets with target-induced etching reaction. Issue 48 (21st November 2018) - Zeng, Ruijin; Tang, Yun; Zhang, Lijia; Luo, Zhongbin; Tang, Dianping
Abstract : In this study, we designed a novel dual-readout biosensing protocol for quantitative or qualitative screening of antibiotic residues (Kanamycin; Kana used in this case) using a spectrofluorometer and via naked-eye detection. Abstract : In this study, we designed a novel dual-readout biosensing protocol for quantitative or qualitative screening of antibiotic residues (Kanamycin; Kana used in this case) using a spectrofluorometer and via naked-eye detection. This assay comprises two sequential reactions: target-aptamer binding to trigger Exonuclease I (Exo I)-assisted target recycling and a three-way junction-assisted hybridization chain reaction (3WJ-HCR). Gold nanocluster-functionalized manganese dioxide nanosheets (AuNCs-MnO2 ) were synthesized via a one-pot biomimetic mineralization process and used as signal-generation tags because of the quenching efficiency of MnO2 toward the AuNC's fluorescence. Upon addition of Kana analyte, target-assisted recycling and the 3WJ-HCR reaction were readily implemented on functional magnetic beads, thus resulting in the assembly of numerous alkaline phosphatase (ALP) molecules through the avidin-biotin interaction, which hydrolyzed ascorbic acid 2-phosphate (AAP) to ascorbic acid (AA). The as-prepared AA etched the MnO2 nanosheets into Mn 2+ to release the carried AuNCs, thereby recovering the fluorescence of the AuNCs. Meanwhile, visual detection could be performed according to the change in the color of AuNCs-MnO2 . Under optimum operating conditions, the intensity of fluorescence increased with the increase in Kana within a dynamic working range from 0.002 nM to 5 nM, with a limit of detection (LOD) of 1.2 pM. A cutoff value of 50 pM Kana could also be obtained in the visual assay on the basis of change in the color from brown to white. In addition, the precision, reproducibility, and selectivity of this method were acceptable. For the analysis of real milk samples with Kana, well-matched results were acquired between the developed fluorescence assay and the referenced Kana enzyme-linked immunosorbent assay (ELISA) kit.